ANALISIS KESALAHAN PADA PROSES PRA ANALITIK DAN ANALITIK TERHADAP SAMPEL SERUM PASIEN DI RSUD BUDHI ASIH - enny khotimah (Yayasan Pendidikan Medika Indonesia, 2022)
Laboratory services are one of the supporting factors in the health service sector. There are three important stages that play a role in the laboratory examination process, namely pre-analytical, analytical and post-analytical. Errors in the pre-analytics process can reach 68%, errors in the analytical stage reach 13%, and errors in the post-analytical stage by 19%. A bad sample will give invalid laboratory examination results. This research was conducted in the laboratory of Budhi Asih Hospital with research respondents of the laboratory officers of Budhi Asih Hospital. The results of the study obtained for serum examination at the pre-analytical stage started from patient preparation getting a score of 80.4% with an excellent category, giving patient identity got a score of 60% sufficient, spesimen collection got a score of 78.8% with a good category and the last one for spesimen storage got a score of 60% with sufficient categories. The total score for the laboratory examination stage in this pre-analytical stage was 79.2% with a good category. The results of the scores at the analytical stage in this study for the spesimen processing category obtained 85% results with an excellent category, the use of tools 86.6% with excellent categories, spesimen examination 75.8% with a good percentage. The total score for the analytical stage in this study got a result of 82.7% with an excellent category.